Application of 1-Hydroxy-4,5-Dimethyl-Imidazole 3-Oxide as Coformer in Formation of Pharmaceutical Cocrystals - Aneta Wróblewska; Justyna Śniechowska; Sławomir Kaźmierski; Ewelina Wielgus; Grzegorz D. Bujacz; Grzegorz Mlostoń; Arkadiusz Chworos; Justyna Suwara; Marek J. Potrzebowski (MDPI AG, 2020)
Two, well defined binary crystals with 1-Hydroxy-4,5-Dimethyl-Imidazole 3-Oxide (HIMO) as coformer and thiobarbituric acid (TBA) as well barbituric acid (BA) as Active Pharmaceutical Ingredients (APIs) were obtained by cocrystallization (from methanol) or mechanochemically by grinding. The progress of cocrystal formation in a ball mill was monitored by means of high-resolution, solid state NMR spectroscopy. The 13C CP/MAS, 15N CP/MAS and 1H Very Fast (VF) MAS NMR procedures were employed to inspect the tautomeric forms of the APIs, structure elucidation of the coformer and the obtained cocrystals. Single crystal X-ray studies allowed us to define the molecular structure and crystal packing for the coformer as well as the TBA/HIMO and BA/HIMO cocrystals. The intermolecular hydrogen bonding, π-π interactions and CH-π contacts responsible for higher order organization of supramolecular structures were determined. Biological studies of HIMO and the obtained cocrystals suggest that these complexes are not cytotoxic and can potentially be considered as therapeutic materials.